A molecular phylogeny of Phasmatodea with emphasis on Necrosciinae, the most species‐rich subfamily of stick insects. (9th February 2014) - BRADLER, SVEN; ROBERTSON, JAMES A.; WHITING, MICHAEL F.
Abstract The phasmatodeans or stick and leaf insects are considered to be a mesodiverse insect order with more than 3000 species reported mainly from the tropics. The stick insect subfamily Necrosciinae comprises approximately 700 described species in more than 60 genera from the Oriental and Australian region, forming the most species‐rich subfamily traditionally recognized within Phasmatodea. However, the monophyly of this taxon has never been thoroughly tested and the evolutionary relationships among its members are unknown. We analyse three nuclear (18S and 28S rDNA, histone 3) and three mitochondrial (COII, 12S and 16S rDNA) genes to infer the phylogeny of 60 species of stick insects that represent all recognized families and major subfamilies sensu Günther and the remarkable diversity within Necrosciinae. Maximum parsimony, maximum likelihood and Bayesian techniques largely recover the same substantial clades, albeit with highly discordant relationships between them. Most members of the subfamily Necrosciinae form a clade. However, the genus Neohirasea – currently classified within Lonchodinae – is strongly supported as subordinate to Necrosciinae, whereas Baculofractum, currently classified within Necrosciinae, is strongly supported within Lonchodinae. Accordingly, we formally transfer Neohirasea and allied taxa (namely Neohiraseini) to Necrosciinae sensu nova (s.n.) and Baculofractum to Lonchodinae s.n. We also provide further evidence that Leprocaulinus, until recently recognized as Necrosciinae, belongs to Lonchodinae, and forms the sister taxon of Baculofractum. Furthermore, Lonchodinae is paraphyletic under exclusion of Eurycantha and Neopromachus. We reinstate the traditional view that Neopromachus and related taxa (Neopromachini sensu Günther) are a subgroup of Lonchodinae and transfer those taxa + the New Guinean Eurycanthinae accordingly. Morphological evidence largely corroborates our molecular‐based findings and also reveals that Menexenus fruhstorferi is a member of the genus Neohirasea and is thus transferred from Menexenus (Lonchodinae) to Neohirasea, as Neohirasea fruhstorfericomb.n. (Necrosciinae s.n.). Other phylogenetic results include Areolatae and Anareolatae each supported as polyphyletic, Heteropteryginae and Lanceocercata (Bayesian analysis) are monophyletic, albeit with low support, and Necrosciinae s.n. and Lonchodinae s.n. are recovered as sister taxa (Bayesian analysis).